Acute macular neuroretinopathy occurrence in a Behçet disease patient: a case report - Ayman Mabchour; Moncef Ould Hamou; Simon Correa; François Willermain; Nacima Kisma (Journal of Ophthalmic Inflammation and Infection)
Abstract Purpose To report the occurrence of AMN (Acute Macular Neuroretinopathy) in a Behçet Disease (BD) patient during an active systemic inflammatory relapse and to describe the SD-OCT features of this entity. Patients and methods Retrospective observational case report of a patient who presented with an AMN during a BD associated ocular inflammation (Saint Pierre Hospital, Brussels, Belgium). Clinical record and imaging, including infrared reflectance image (IR) and spectral domain optical coherence tomography (SD-OCT), were analyzed. Results A 25-year-old man presented with an acute right eye scotoma due to AMN in the setting of active systemic BD. Oral corticosteroid therapy and corticosteroid sparing agents (azathioprine) were prescribed. Close observation revealed progressive lesion regression. Conclusion In conclusion, the association between AMN and BD may occur in the context of active systemic disease, though further studies are required to better establish this link. Vigilance appears warranted during inflammatory episodes in BD, as they might contribute to such manifestations. Clinicians could consider BD as a potential differential diagnosis in patients presenting with features suggestive of AMN, and neurological involvement may merit cerebral imaging to exclude other causes. Additionally, the management of posterior uveitis in BD, if present, may benefit from timely and targeted treatment. Further investigations are necessary to refine management strategies for AMN in patients with BD.